1988
DOI: 10.1002/app.1988.070350117
|View full text |Cite
|
Sign up to set email alerts
|

Common thermoanalytical characteristics of durable press reactants based on cyclic ureas

Abstract: SynopsisThermal analyses, including differential scanning calorimetry (DSC), thermogravimetry (TG), and differential thermogravimetry (DTG), were performed on a series of derivatives of cyclic ureas under nitrogen. Such compounds are used extensively for durable press finishing of cotton textiles. Three common features were discovered in 15 compounds analyzed. T w o features related to the presence of an oxygen-containing substituent on the ring carbons or the ring nitrogens. The former substitution was expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…4,5-Diethoxyethyleneurea produced both ions. The three 4,5-dialkoxyethyleneureas produced an exotherm during thermal analyses (Trask-Morrell and Kottes Andrews, 1988), and this exothermic activity may have increased the rate of vaporization, leading to higher pressures in the source region of the instrument. This explanation does not hold for the '-dimethyl-4,5-dihydroxyethyleneurea compound which does not produce an exotherm in TA but does produce both [M]+ and [M + 1]+ ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5-Diethoxyethyleneurea produced both ions. The three 4,5-dialkoxyethyleneureas produced an exotherm during thermal analyses (Trask-Morrell and Kottes Andrews, 1988), and this exothermic activity may have increased the rate of vaporization, leading to higher pressures in the source region of the instrument. This explanation does not hold for the '-dimethyl-4,5-dihydroxyethyleneurea compound which does not produce an exotherm in TA but does produce both [M]+ and [M + 1]+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…ring carbons included OH, OCH3, and OC2H5. These reactants are described in detail in our earlier publication (Trask-Morrell and Kottes Andrews, 1988), and their structures are drawn on the figures within the text. The compounds are named in the manner common to textile chemists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its DSC thermogram showed the compound melting and decomposing in two peaks. The corresponding TG curve had associated weight losses of 11 and 72%, respectively, and left a moderate amount of residue.…”
Section: Tricarboxylic Acidsmentioning
confidence: 99%
“…with finish development. Our basic research studies were concerned with durable press reactants themselves, both formaldehyde [4] and nonformaldehydebased [ 5 ], various catalysts, and mixtures of reactants and catalysts [ 6 ] . We analyzed treated fabrics next to determine if the thermal characteristics were measurably different from untreated fabric and found that they were [ 7 ] .…”
mentioning
confidence: 99%